Relação espacial entre a falange distal e o estojo córneo em equinos da raça Campolina com e sem sinais de obesidade - Jessica Fontana de Magalhaes (2015)
Previous studies have demonstrated radiographic changes in the hoof of obese horses. The objectives were to study through radiographic evaluation the spatial relationship between the hoof capsule and the distal phalanx of Campolina mares with and without obesity. 49 Campolina mares were used, 38 mares were examined during the breeders national exhibition and 11 coming from Entre Rios de Minas, MG farms. We analyzed adiposity variables and radiographic measurements of the hoof of both forelimbs of mares with body condition score from 5 to 7/9 (Control group) and from 8 to 9 (Obese group) considering two different age groups: young mares (3-5 years) and adult mares (6-14 years). Comparisons were made between groups using the Student t test for parametric variables and the Mann-Whitney test for the nonparametric ones. Pearson or Spearman tests were used to evaluate the correlation among parametric and nonparametric variables respectively (P <0.05). Results showed that obese Campolina mares presented changes in the spatial relationship between the hoof capsule and the distal phalanx, especially an increasing founder distance in the adult ones. The intensity of these changes occurs in proportion to the increase in subcutaneous fat accumulation, especially in the neck. These findings corroborate previous studies in Criollo and Mangalarga Marchador breeds and indicate that obesity predisposes Brazilian horses to endocrinopathic laminitis.